GENERATION AND SIMULATION OF MESHING FOR INVOLUTE HELICAL GEARS (Journal of Engineering, 2009)
A new method for generation and simulation of meshing for involute helical gears is presented. Theapproaches proposed for generation are based on the imaginary application of two rack-cutters onefor pinion and the other for gear generation. The proposed simulation of meshing of aligned andmisaligned helical gears gives (i) the shift of the bearing contact (real contact path) on pinion andgear tooth surfaces, (ii) the function of transmission errors.